Long-term simulations of particulate matter in Europe on different scales using sequential nesting of a regional model. (14th October 2004) - Memmesheimer, M.; Friese, E.; Ebel, A.; Jakobs, H.J.; Feldmann, H.; Kessler, C.; Piekorz, G.
A regional model system for the simulation of air quality in Europe (EURAD) has been employed for long-term calculations of atmospheric pollutants on different scales. The model allows sequential nesting. Starting with a domain covering most of Europe, the nesting procedure was used to scale down the simulations to a highly populated and industrialized area, namely NorthRhine-Westphalia (NRW). The analysis of results is focusing on the simulation of particulate matter (PM10 ) for the year 1997. This parameter is of special interest in the framework of air pollution control as demanded by the European Union. The model takes account of various components of the atmospheric aerosol, including secondary organic aerosols (SOA). Their role in the budget of particulate matter is briefly shown. The model data are compared with measurements of the monitoring network of NRW. Hit rates for a given range of accuracy are discussed for PM10 and NO2 . It is found that a large part of deviating results may be ascribed to shortcomings in the applied aerosol emission inventories, in particular, and that it is worthwhile to improve them for the application to future air quality assessments based on numerical simulations.